Impact of the COVID-19 pandemic on oral oncolytic adherence. Issue 28 (1st October 2022) - McAuliff, Kelly; Rutter, Wilbur; Cavers, William; Shah, Dipti; Pittos, Elias; Feczko, Lucia; Grover, Rashmi; Avalos-Reyes, Elisea; Johnson, Kjel Andrew
Abstract : 395 Background: COVID-19 has substantially decreased cancer screening, management visits and surgeries. CVS Health recently developed a best-in-class mobile app and website that enables oncology patients to start and stay on therapy. This study examined the impact of COVID-19 on adherence to oral oncolytic agents in a large health plan with a significant digital health platform. Methods: This retrospective cohort study included adult patients with chronic myelogenous leukemia (CML), ovarian cancer or prostate cancer initiating oral oncolytics between 3/1/19 and 3/1/2021. Patients were divided into two groups: pre-COVID oral oncolytic initiators before 3/1/20 and COVID initiators after 3/1/20 and were followed for 1 year after therapy initiation. The primary outcome was optimal adherence to oral oncolytic agents as defined by a medication possession ratio (MPR) ≥ 0.8. Percent of digital engagement, defined as the number of times a patient interacted with the CVS digital platform, was examined as a secondary endpoint and was considered as a binary and categorical endpoint (none, low (< 28), moderate (28-105) and high (> 105)). Descriptive statistics and logistic regression modeling were performed; p-values < 0.05 were significant. Results: In total, 15, 494 patients were included in the study, with 8, 067 (52.07%) in the pre-COVID initiator group. Patient demographics were similar across study groups, with the exception of pre-COVID initiators who were less likely to be male (75.32% vs. 77.34%; p < 0.01) and receive copay assistance (38.37% vs. 41.70%; p < 0.01). No difference in digital engagement pre and during COVID was noted (74.55% vs. 73.60%; p = 0.18). Pre-COVID initiators were less likely to be optimally adherent than COVID initiators (84.75% vs. 85.96%; p = 0.04). Therapy persistence was more common among COVID initiators, with greater number of fills (Median [quartile (Q) Q1-Q3]: 10 [4-12] vs. 9[4-12]; p < 0.01) and less changes to therapy (8.87% vs. 9.95%; p = 0.02). After regression, COVID initiation of oral oncolytics was not associated with optimal adherence (odds ratio (OR) = 1.06 [95% (confidence interval (CI) 0.96-1.16]). Adherence increased as digital engagement increased (low: OR 0.64 [95% CI 0.56-0.72]; moderate: OR 0.67 [95% CI 0.56-0.76]; high: OR 1.71 [95% CI 1.48-1.99]). Other factors associated with increased adherence were copay assistance, male gender and age between 65 and 84 (all p < 0.05). Factors associated with decreased adherence were therapy change, CML and age < 50 years (all p < 0.05). Conclusions: The onset of the COVID-19 pandemic did not significantly impact optimal adherence for new-to-therapy oral oncology patients. Patients with high digital engagement during the pandemic experienced significantly improved adherence than those not engaged. Additionally, persistence and number of fills were slightly improved in COVID initiators, suggesting that the current pandemic may have influenced adherence behaviors.